(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the impact of AI tools on research writing, highlighting benefits like task streamlining and enhanced data analysis. However, concerns arise regarding academic integrity and critical thinking. Despite challenges, judicious AI use holds promise for revolutionizing scholarly writing. Integration into education fosters awareness of ethical implications. Researchers must balance AI benefits with skill development to maintain integrity. Embracing AI as a complement to human judgment is crucial for navigating research writing ethically.